HUBUNGAN ANTARA PEKERJA LAS LISTRIK DENGAN KEJADIAN KATARAK PADA BEBERAPA BENGKEL LAS DI KOTA MANADO - Fransiska Lintong (EKOTON, 2014)
Electrical welding is the metal joining process by using electrical power as the source of heat. During the welding process a very sharp light will occur that endanger the workers and other people nearby the welding site. These lights include the visible light, ultraviolet, and infrared. The ultraviolet and infrared lights are the physical factors that could create a disease to the eyes, particulary cataract. The aim of this research was to identify the relationship between the Electrical Welding Workers with the Incidence of Cataract in Manado. This work is an observational research with cross – sectional design. The research locations were Makmur Jaya (Wanea District), Esi Advertising (Mapanget District), Rapi Jaya, and Sinar Karya (Tikala District) welding workshops. The research subject were 40 electrical welding workers (exposed) and 20 not electrical welding workers (unexposed) that fulfilled the inclusion criterion. The data was collected through the interview by using questionaire and a special examination of eyes by an Ophthalmologist. To examine the cataract loupe and Slit Lamp were used. The data were analyzed by using Fisher Exact Test. The result of statistic analysis by using Fisher Exact Test showed that there was no a significant relationship between the electrical welding workers with the incidence of cataract in Manado ( p = 0,289).